Response of Growth Bud Chip Seeds Sugarcane (Saccharum officinarum L.) on the Distance between Pot Tray and Leaf Clypping - Gede Raharjo Purwo Wardoyo (Jurnal Agroekoteknologi, 2017)
Response of Growth Bud Chip Seeds Sugarcane (Saccharum officinarum L.) on the Distance between Pot Tray and Leaf Clypping. Supervised by ROSITA SIPAYUNG and T. SABRINA. The aims of this study was to determine research the effect of distance between Pot Tray and leaf clypping on the growth of bud chip seeds sugarcane. This research was held at the nursery area of the Research and Development Center PTPN II, Sei Semayang from November 2015 to January 2016. Experiment design used was a split plot design with two factors, the first factor was distance between Pot Tray (0, 10, 20 and 30 cm) and the second factor was leaf clypping (control, on 4 weeks after planting (WAP) and on 8 WAP). The result showed that the distance between Pot Tray effected to the plant height, the number of leaf and the number of tillers significantly. The highest yield was found treatment on the distance between Pot Tray 20 cm (J2), whereas shoot dry the highest weight and seedling quality index was found treatment on the distance between Pot Tray 30 cm (J3). Leaf clypping treatment effected to the seedling quality index with the highest yield was found at treatment without clypping (0,42). Meanwhile the interaction of both treatments effected to the number of tillers (0,84), with highest yield was found at combination treatment J2P1 (the distance between Pot Tray 20 cm and clypping on 4 WAP). Key word : bud chip, leaf clypping, sugarcane, the distance between Pot Tray